The Caldes Strain (Spain) - Gómez E.A.; Rafel O.; Ramón J. (Rabbit genetic resources in Mediterranean countries, 2002)
A brief description of a Spanish strain of rabbits, Caldes, selected for postweaning growth rate is reported. A general description of the population and some performances are presented. Notes about genetic parameters of economic traits are also included.